Economic Benefits of Export Diversification in Small States - McIntyre, Arnold (IMF Working Papers; Working Paper, 2018)
The paper considers concepts of economic diversification with respect to exports (including service sectors) for small states. We assessed the economic performance of different groups of 34 small states over the period of 1990-2015 and found those more diversified experienced lower output volatility and higher average growth than most other small states. Our findings are consistent with conventional economic theories but we found that export diversification has a more significant impact on reducing output volatility than improving long run growth in small states. Diversification requires fundamental changes and should be contemplated in the context of a cohesive development strategy.